Análise de sistemas convectivos de mesoescala em São Luís – MA: estudo de caso do dia 02 de maio de 2009 - CASTRO, Robson Santino Gomes (2019)
Mesoscale convective systems (MCS) are constituted by a cluster of convective clouds and presenting area with continuous precipitation which can be partially stratiform and convective partially, have various shapes. They can be classified as: Instability lines (LI), those having the line shape; Mesoscale convective complex (MCC), those having a circular shape or simply, SCM, the irregular shapes. The passage of these systems is usually accompanied by heavy rainfall and strong wind gusts. This analysis was used brightness temperature data in the infrared channel satellite Geostationary Operational Environmental Satellite (GOES) provided by the National Aeronautics and Space Administration (NASA), in order to identify the cloud tops, which are collected from 30 to 30 minutes with a spatial resolution of 4 km, is useful in observing the life cycle of SCMs. To identify the regions of more convective systems. the images in the microwave channel were used, infrared and weather radar from the TRMM group Precipitation Measuring Missions (PMM), the University of Utah. The study was conducted for the city of São Luís, State of Maranhão, which is located in North mesoregion Maranhense and micro urban agglomeration of São Luís. The results show the squall lines (SLs), typically are formed along the north-northeast coast of South America from Guyana to the state of Maranhão, and some of these lines of cumulonimbus propagate into the Amazon Basin and other dissipate near the Atlantic coast. The origin of both lines of cumulonimbus that propagate, as those that do not propagate, is associated with the sea breeze circulation along the coast.